THE INFLUENCE OF VOLCANIC MATERIALS ON THE PROPERTIES OF PADDY SOILS - PRASETYO, BAMBANG HENDRO; SUGANDA, HUSEIN; KASNO, ANTONIUS (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2007)
Three pedons of paddy soils classified as Oxyaquic Eutrudepts from Pati, Typic Endoaquerts from Ngawi and Vertic Endoaquepts from Klaten have been studied pedogenetically based on their physical, mineralogical and chemical properties. For this purpose as many as 15 soil samples were analyzed in Laboratory. The results indicated that all pedons were influenced by different materials. The top soil of paddy soil from Pati wascovered by sediment material which was dominated by quartz, while sub soils was influenced by volcanic materials consist of association labradorite-hornblende minerals. Paddy soil from Ngawi continuously influenced by volcanic materials in all profile with association of labradorite-hornblende, while paddy soil from Klaten which was derived from volcanic alluvium showed domination of primary mineral in their association, e.g labradoritehornblende- augite-hypersten. The clay mineral composition in all paddy soils were dominated by smectite, with a lesser extends kaolinite and halloysite. The higher content of kaolinite in the top layer of paddy soil from Pati was formed from sediment materials, while in all sub soils kaolinite and haloisite were formed from weathering of labradorite from volcanic materials. Chemically, all pedons are fertile, the main difference is on the ratio of Ca/Mg. Paddy soils from marl (Pati and Ngawi) have Ca/Mg ratio ranging between 5:1 and 12:1, while paddy soil from alluvium (Klaten) is about 2:1. The influence of volcanic materials gives a positive impact on paddy field properties, especially in the source of nutrients but could not modify the Ca/Mg ratio.